First successful experience of the Zenker's diverticulum endoscopic therapy in Kazakhstan - Kanat Batyrbekov; Alexey Zelenyy; Ainur Galiakbarova (LLC "MEDIAFORMAT", 2020)
Zenker's diverticulum tends to occur in the elderly and is generally a relatively rare disorder; the prevalence of Zenker's diverticulum is 1.5-5% of all esophageal diverticula. Men are affected 2-3 times more frequently than women. To date, Zenker's diverticulum is treated mostly by surgery in Kazakhstan, however, with the development of endoscopy the minimally invasive method, endoscopic diverticuloesophagostomy, is being implemented. The transoral treatment is aimed at creating the common cavity between the esophagus and the diverticulum in order to prevent food accumulation in the diverticulum. The anterior wall between these two structures consists of the diverticular wall, m. сricopharyngeus and esophagus wall, the septum transsection automatically ensures myotomy. Both open surgery and endoscopic transoral treatment of Zenker's diverticulum result in reduced symptoms in 94-100% of patients. The paper reports the first successful experience of the Zenker's diverticulum treatment by endoscopic submucosal tunnel dissection in Kazakhstan.